Efektivitas Antimikroba Minyak Zaitun Sebagai Bahan Tambahan Pasta Gigi Terhadap Bakteri Streptococcus mutans - Rahmawati Nur Annisa; Murni Mursyid (Universitas Sulawesi Barat, 2020)
Maintaining healthy teeth and mouth was very important because in the mouth area there are various kinds of bacteria that can interfered with the health of the teeth and body health. Dental caries is a form of tooth decay that occurs due to the buildup of plaque on the teeth due to the accumulation of Streptococcus mutans bacteria on the tooth surface. Prevention of caries in teeth is generally carried out, namely controlling the formation of plaque on teeth by mechanical means (brushing the teeth) and coupled with the use of toothpaste as an additive to overcome the growth of S. mutans. This study aimed to determine the antimicrobial activity of toothpaste with olive oil as an additional ingredient against S. mutans. Toothpaste made with additional olive oil in various concentrations, namely 10, 15 and 20%, the control toothpaste was the toothpaste that was not given additional oil. The antimicrobial activity of toothpaste was tested by using agar diffusion method using disc paper. The results showed that toothpaste with the addition of olive oil at concentrations of 10, 15 and 20% had antimicrobial activity against S. mutans with zone values ​​of 24.55 each; 26.25; and 28.25 mm. The biggest zone of resistance is 28.25 mm at an additional concentration of 20% oil.